Differences in force production and EMG activity on underwater and dry land conditions in swimmers and non-swimmers - Hermosilla Perona, F.; Machado, L.; Sousa, F.; Vilas-Boas, J. P.; González Ravé, J. M. (Sports Biomechanics, 2024)
This research aims to provide a better understanding of the swimming push-off specificity comparing force production and electromyographic (EMG) activity on squat-jumps (SJ) and countermovement-jumps (CMJ) performed underwater (similar to swimming turns push-off) and dryland conditions on two different level of expertise participants (swimmers and non-swimmers). Thirteen male swimmers and nine non-trained male sport sciences students participated in this study. Each subject carried out 10 CMJ and 10 SJ jumps in dryland (vertical) and underwater (horizontal). During these trials, force production was recorded by force platforms and muscular activity of Vastus Lateralis, Biceps Femoris, Gastrocnemius Medialis and Tibialis Anterior was analysed through EMG. A three-way ANOVA showed that swimmers increased the differences in values obtained from SJ to CMJ between dry and underwater conditions during the first impulse phase-Impulse 1 (p < 0.01), the second phase of impulse-Impulse 2 (p < 0.001) and duration from peak force to take off (p < 0.001) in contrast to non-swimmers. Patterns relating to force production and EMG were non-consistent between muscles. Jumping performance was not significantly correlated between dry land and underwater conditions; nevertheless, results emphasise that environmental constraints are decisive to define the neuro-motor response to apparently similar tasks performed in different contexts.